Prognostic value of ABCDE stress echocardiography. (14th October 2021) - Ciampi, Q; Zagatina, A; Cortigiani, L; Wierzbowska-Drabik, K; Haberka, M; Djordjevic-Dikic, A; Boshchenko, A; Gaibazzi, N; Rigo, F; Simova, I; Barbieri, A; Morrone, D; et al.
Abstract: Background: Stress echocardiography (SE) was recently upgraded to the ABCDE protocol: step A, regional wall motion abnormalities; step B, B-lines; step C, left ventricular contractile reserve; step D, Doppler-based coronary flow velocity reserve in left anterior descending coronary artery; and step E, EKG-based heart rate reserve. Aim: to assess the prognostic value of ABCDE-SE in a prospective, large scale, multicenter, international, effectiveness study. Methods: From July 2016 to November 2020, we enrolled 3, 574 all-comers (age 65±11 years, 2, 070 males, 58%; ejection fraction 60±10%) with known or suspected chronic coronary syndromes referred from 13 certified laboratories. All patients underwent ABCDE-SE. The employed stress modality was exercise (n=952, with semi-supine bike, n=887, or treadmill, n=65 with adenosine for step D) or pharmacological stress (n=2, 622, with vasodilator, n=2, 151; or dobutamine, n=471). SE response ranged from score 0 (all steps normal) to score 5 (all steps abnormal). All-cause death was the only end-point. Results: Rate of abnormal results was 16% for A, 30% for B, 36% for C, 28% for D and 37% for E step. During a median follow-up of 21 months, 73 deaths occurred. At univariable analysis, predictors of all-cause mortality were step B (hazard ratio, HR: 2.621, 95% Confidence Intervals, CI: 1.654–4.152, p<0.001), step D (HR: 2.578, 95% CI: 1.624–4.093, p<0.001), and step E (HR: 2.955, 95% CI: 1.848–4.725, p<0.001), but not step A (HR: 1.333, 95% CI: 0.731–2.430, p=0.349) and step C (HR1.581, 95% CI: 0.997–2.506, p=0.051). At multivariable analysis, ABCDE-SE was an independent predictor of mortality with score 3 (HR: 3.472, 95% CI: 1.483–8.135, p=0.004), 4 (HR: 4.045, 95% CI: 1.595–10.259, p=0.003) and 5 (HR: 5.678, 95% CI: 2.106–15.313, p=0.001) (Figure). Annual mortality rate ranged from 0.4% person/year for score 0 up to 2.4% person/year for score 5. Conclusion: ABCDE-SE allows an effective risk stratification of patient global vulnerability. Funding Acknowledgement: Type of funding sources: None.